2015
DOI: 10.4172/2161-0509.s1-006
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction An Approach towards Obesity Management

Abstract: Obesity is increasing worldwide and has become a public health concern due to associated degenerative diseases and morbidity. Even though overweight and obesity are not life threatening, they qualify themselves as a disease entity. The bulk of literature on obesity says that the external environment largely influences the increase in food intake and is termed scientifically as "obesogenic environment". A "dual approach" that uses both traditional and holistic health can be used to curb this rising trend. Dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Calorie restriction [10] is the major form of dietary restriction, and means reducing calorie intake by about 15-40% while maintaining sufficient amounts of essential nutrients, vitamins, and minerals [11][12][13] . For the first time in 1913, Osborne et al reported that decreasing food intake in rats resulted in an increased lifespan [14] .…”
Section: Hints For Therapeutic Interventions Through Exploring the Efmentioning
confidence: 99%
See 1 more Smart Citation
“…Calorie restriction [10] is the major form of dietary restriction, and means reducing calorie intake by about 15-40% while maintaining sufficient amounts of essential nutrients, vitamins, and minerals [11][12][13] . For the first time in 1913, Osborne et al reported that decreasing food intake in rats resulted in an increased lifespan [14] .…”
Section: Hints For Therapeutic Interventions Through Exploring the Efmentioning
confidence: 99%
“…For the first time in 1913, Osborne et al reported that decreasing food intake in rats resulted in an increased lifespan [14] . Since then, much money and effort have been dedicated to these kind of studies, with the majority suggesting that calorie restriction is the most robust form of intervention, one which can extend lifespan and reduce ageassociated diseases [12,15,16] . According to the US Practice Guideline for the Diagnosis and Management of NAFLD and other scientific societies interventions which lead to weight loss, either by hypocaloric diet alone or in conjugation with physical activity, can reduce hepatic steatosis [17][18][19] .…”
Section: Hints For Therapeutic Interventions Through Exploring the Efmentioning
confidence: 99%
“…At the same time, the management of overweight and obesity is considered a major modifiable intervention in the prevention of CVD as the leading cause of death worldwide (3) . A common interventional approach to combat obesity and associated metabolic disorders is energy restriction (4) . Nevertheless, weight reduction during energy restriction alone is associated with the remarkable decrease in fat free mass (FFM), energy expenditure, fat oxidation, and satiety, all lead to increased risk of weight regain and metabolic disorders (5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…A CR regimen is generally carried out through the reduction of calorie intake by up to 20%–40% of ad libitum (AL), whereas adequate nutrient intake is maintained. [ 1 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, fewer cases of heart disease, hypertension, and diabetes were reported. [ 1 ] Furthermore, the incidence of cancer was lower than expected among Norwegian women who went through puberty during the food shortages of World War II. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%